Experimental Study on the Mud-Water Inrush Characteristics through Rock Fractures - YanLin Zhao; LianYang Zhang (Advances in Civil Engineering)
Fractured rock masses, which are widely distributed in the south of China, have an impartible relationship with mud-water inrush. In order to study the change laws of mud viscosity under different moisture content, flow property, and mechanism of mud-water inrush in fractured rock masses, a NDJ-8S rotary viscometer and a simulation model are used to carry out a series of experimental studies. Tests of mud viscosity show that mud viscosity depends on moisture content, and the relationship between viscosity and moisture content was proposed. Based on mud viscosity results, physical model tests’ results indicated that the process of mud-water rush can be divided into four stages: that is, the preparation stage of mud-water mixture burst, the seepage period of mud-water mixture inrush, the nonstable period of mud-water mixture outburst, and the stable period of mud-water mixture outburst. The excavation disturbance, high water pressure, and effect of erosion and corrosion of water were identified as key factors which lead to mud-water inrush in fractured rock masses